SURVIVAL OF LIVER CELLS, IMMOBILIZED ON 3D-MATRIXES, IN LIVER FAILURE MODEL - M. Y. Shagidulin; N. A. Onishchenko; M. E. Krasheninnikov; I. M. Iljinsky; N. P. Mogeiko; N. P. Shmerko; A. A. Andriyanova; P. V. Avramov; E. A. Nemets; V. I. Sevastjanov; S. V. Gautier (Вестник трансплантологии и искусственных органов)
It was examined a new method for correction of hepatic failure by transplantation of liver support biounit (liver cells, immobilized on biocompatible and biodegradable 3D-matrixes ElastoPOB®) into small intestine mesentery. It was determined that after modeling of acute hepatic failure on dogs by 65–70% liver resection) and transplantation liver support biounit the restoration of disturbed biochemical indecies (such as total protein, lactate, cytolytic ensymes-ALT, AST, ALP, LDH, fibrinogen, protrombine index and others) took place more rapidly on 9–14th day instead of 18th day in control. It was made a preposition about efficiency of the suggested method for correction both acute hepatic failure because even 90 days after transplantation of liver support biounit alive hepatocytes and neogenic plethoric vessels, growing through matrix were revealed.